The Role of Schools Driving the Implementation of the Independent Curriculum at SDN Palumbonsari IV Karawang - Rizal Syaefi Abdurahman; Amirudin, Amirudin; Iqbal Amar Muzaki (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this research is to identify and obtain information about the implementation of the independent curriculum in SDN Palubonsari IV driving schools. The method used in this study is a qualitative descriptive method, which describes the subject about the situation and data obtained during observations and questions so that it becomes useful information and is easily understood by readers. This study explains and provides an overview of the implementation of the independent curriculum in driving schools. The results of this study indicate that the implementation of the curriculum in driving schools has been carried out optimally and is ongoing, although in its implementation there are still many shortcomings and obstacles. The key to success in implementing the curriculum in driving schools is that the principal and teachers must have the will to make changes. The principal as a leader must be able to change the mindset of the Human Resources in the school to make changes so that the independent curriculum can be implemented at SDN Palumbonsari IV.